2019
DOI: 10.1002/phar.2352
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Administration by Untrained Community Members

Abstract: Study ObjectiveAccess to naloxone is a priority for reducing opioid deaths. Although community members who complete naloxone training are able to administer nasal naloxone successfully and rapidly, little is known about the ability of community members to administer naloxone without training. The objective of this study was to assess the ability of untrained individuals to administer naloxone successfully in a simulated opioid overdose setting.DesignProspective single‐site open‐label randomized usability asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Because direct observations of laypersons behavior in real overdose situations are generally not feasible, due to the unpredictable nature of overdoses, some researchers have attempted to measure overdose response proficiency (i.e., how well laypersons are able to translate what they have learned during training into behavior) in a simulated overdose situation. These studies indicate variations in the ability of trained laypersons to administer naloxone (Eggleston et al, 2018 , 2020 ). While our study and others have shown that commonly used OEND practices lead to improved opioid overdose knowledge and attitudes toward overdose management (Clark et al, 2014 ; European Monitoring Centre for Drugs & Drug Addiction, 2015 ; McDonald & Strang, 2016 ), continued research addressing the gap between intended or anticipated behavior and actual behavior is required to clarify the real-world implications of these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because direct observations of laypersons behavior in real overdose situations are generally not feasible, due to the unpredictable nature of overdoses, some researchers have attempted to measure overdose response proficiency (i.e., how well laypersons are able to translate what they have learned during training into behavior) in a simulated overdose situation. These studies indicate variations in the ability of trained laypersons to administer naloxone (Eggleston et al, 2018 , 2020 ). While our study and others have shown that commonly used OEND practices lead to improved opioid overdose knowledge and attitudes toward overdose management (Clark et al, 2014 ; European Monitoring Centre for Drugs & Drug Addiction, 2015 ; McDonald & Strang, 2016 ), continued research addressing the gap between intended or anticipated behavior and actual behavior is required to clarify the real-world implications of these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were able to conclude that the nasal spray formulation of naloxone was the most successfully administered in an opioid overdose. 19 Crucial data obtained with the aid of HFS confirm the benefits of its utilization not only in teaching, but also in obtaining information to better advance emergency management and public health.…”
Section: Introductionmentioning
confidence: 95%
“…28 Two recently approved products using each of these routes of administration have been shown to have advantages regarding ease of use and may thus be preferable when increased cost is not a barrier. [29][30][31][32] When used, naloxone can restore normal respiration and consciousness in the overdose victim. 11 Improving access to naloxone has become a national priority endorsed by the Surgeon General, and every state has enacted at least one naloxone access law (NAL) to achieve this goal.…”
Section: Overdose Education and Naloxone Distributionmentioning
confidence: 99%
“…Currently, naloxone is available in several formulations appropriate for administration by a layperson, such as intranasal or intramuscular routes 28 . Two recently approved products using each of these routes of administration have been shown to have advantages regarding ease of use and may thus be preferable when increased cost is not a barrier 29‐32 . When used, naloxone can restore normal respiration and consciousness in the overdose victim 11 .…”
Section: Harm Reductionmentioning
confidence: 99%